2018
DOI: 10.1155/2018/9242718
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Effects of Mobile Phones and Tablets on the Skin: A Systematic Review

Abstract: Background Skin health has become a worldwide concern. Most of the studies investigated the effect of mobile phone radiation on DNA and animals, but a few studies were carried out about skin diseases in mobile phone and tablet users. Few systematic studies have examined the relationship between mobile phone exposure and skin diseases. Methods We evaluated the association between mobile phones and tablets and skin diseases. We checked databases including PubMed, Scopus, Springer, Cochrane, and Google Scholar fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…A few studies were carried out, but no strong evidence associated with the effects of radiation from electronic products on the skin. 45 Our research showed the sebum content of using electronic products more than six hours was higher, and skin surface pH was lower than the other two groups. The date from our research showed using electronic products over 6 hours a day or staying up late causes a decrease in skin pH.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A few studies were carried out, but no strong evidence associated with the effects of radiation from electronic products on the skin. 45 Our research showed the sebum content of using electronic products more than six hours was higher, and skin surface pH was lower than the other two groups. The date from our research showed using electronic products over 6 hours a day or staying up late causes a decrease in skin pH.…”
Section: Discussionmentioning
confidence: 52%
“…With the increasing variety of electronic products and the increasing time for people to use electronic products, more and more people are worried about whether the radiation from electronic products such as smartphones, tablets, and computers will affect our health, especially the skin, which is directly exposed to radiation. A few studies were carried out, but no strong evidence associated with the effects of radiation from electronic products on the skin 45 . Our research showed the sebum content of using electronic products more than six hours was higher, and skin surface pH was lower than the other two groups.…”
Section: Discussionmentioning
confidence: 53%
“…Firstly, the MATLAB coding calculates the impedance and refractive index values of the proposed metamaterial design by utilising the Eqs. (1) and (2), where the signs ′ and ″ described real and imaginary, respectively. Meanwhile, the permittivity and permeability values were directly calculated from Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…Although the 5G network has been highly recommended to comply with current technological advances, it possesses several disadvantages. The radiation exposure from the mobile phone may cause serious health problems such as skin disease, brain tumour, heart disease, irregular blood pressure, sleep disorder, or even cancer [1][2][3][4] . Based on the International Commission on Non-Ionizing Radiation Protection (ICNIRP) and the IEEE C95.1-2019 standards, the SAR limit is set to 2 W/kg for the averaged over 10 g of tissue volume 5,6 .…”
mentioning
confidence: 99%
“…In response to the second issue noted for our study "ignoring the importance of collecting data about using mobile phones in 'standby mode' and 'hands free'," we should accept that lots of variables may be associated to MP use among adolescents. Considering that the current evidence found from systematic/nonsystematic reviews (Karger, 2005, Keykhosravi, Neamatshahi, Mahmoodi, & Navipour, 2018, Moussa, 2011, Roosli, Frei, Mohler, & Hug, 2010 do not provide a consistent pattern that exposure to MPs is hazardous to health, we presumed that using MPs in the "standby mode" and applying "hands free" may not be the case when investigating the associations between MP overuse and mental health. Further research, however, is suggested with considerations on such variables, with the hope to find more rigorous findings.…”
mentioning
confidence: 90%